Cardiac Pathology and Genomics of Sudden Death in Racehorses From New York and Maryland Racetracks. Issue 4 (July 2019) - Molesan, Alex; Wang, Minghui; Sun, Qi; Pierce, Virginia; Desideri, Rhiannon; Palmer, Scott; Todhunter, Rory; Kelly, Kathleen
Postmortem evaluation of racehorses has focused primarily on musculoskeletal injuries; however, horses also die suddenly on the track (sudden death [SD]). Although cardiac conditions are frequently suspected as a cause of death, SD racehorses are often autopsy negative; however, previous studies have been limited due to inconsistent or insufficient cardiac sampling and lack of controls. SD in New York (NY) and Maryland (MD) racehorses was evaluated in an observational case vs control study comparing clinical information, postmortem evaluation including cardiac dissection, and cardiac conduction system histopathology. In the study period, there were 40 cases of SD. In NY, SD occurred in 12% (37/316) of submissions, and 36 (11%) cases of SD were exercise associated (EASD); 3 EASD cases occurred in MD. In NY/MD EASD cases with histologic examination of the heart, 11 of 36 (31%) had significant lesions, including mesenteric artery rupture (1), axial trauma (2), systemic inflammation (2), pulmonary hemorrhage (1), and cardiac disease (5). Mild myocardial fibrosis, mild inflammation, coronary arteriosclerosis, and variation in cardiac nodal connective tissue were present in both SD cases and controls and thus were not considered to be causes of SD. While not excluding a genetic basis for SD, analysis of the genotypes (GGP Equine 70 K Array) of cases and controls did not reveal significant differences in allele frequencies at any locus. Most SD racehorses were autopsy negative; further research using standardized protocols and controls is needed to understand the underlying causes of SD, which is crucial to protecting the viability of racing.